KORELASI TENTANG PENGETAHUAN DAN SIKAP IBU TERHADAP EFEK SAMPING PENGGUNAAN KB IUD DI WILAYAH KERJA PUSKESMAS MOJOTENGAH - Alfiyani, Madinatun; Raharyani, Anisa Ell; Nugraheni, Nazilla (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Background: The Intrauterine Device (IUD) is an effective and long-term contraceptive method. However, a lack of maternal knowledge regarding its benefits and side effects can influence attitudes, such as fear and doubt, which often arise due to inaccurate information. Objective: To determine the relationship between maternal knowledge and attitudes regarding the side effects of IUD contraceptive use in the Mojotengah Public Health Center work area. Method: This study used a quantitative method with a correlational analytic design and a cross-sectional approach. The sample consisted of 46 respondents who were active IUD users at Mojotengah Public Health Center, selected using a total sampling technique. Results: The majority of respondents had low knowledge (71.7%) but showed a positive attitude toward IUD use (65.2%). The Chi-Square test showed a significant relationship between maternal knowledge and attitudes regarding IUD side effects (p = 0.008; r = 0.981), indicating a very strong correlation. Conclusion: There is a significant and strong relationship between maternal knowledge and attitudes toward the side effects of IUD contraceptive use. It is recommended that healthcare providers enhance education for mothers about IUDs to improve understanding and foster more positive attitudes toward this contraceptive method.